Pengaruh Ergonomi dan Antropometri bagi User Gudang Bahan PT. MI guna Meningkatkan Produktivitas Serta Kualitas Kerja - Heri Satria Setiawan (Universitas Indraprasta PGRI Jakarta, 2017)
The Job comfort in a work is a factor having a decisive influence onthe increase of efficiency and effectiveness of work in which the equipment and technology aresome of supporting facilities in improving the productivity of work in a company. Besides inputting data into computers, user operators in PT.MI seat material division also make RF (Receiving Form), receive goods, put goods and make the settings in the material warehouse, bringing about negative effects such as work accidents and occupational diseases. Based on observations and questionnaires distributed to computer warehouse operators, there are some problems creatinguncomfortable and unnatural working condition that lead to less optimal work productivity. Therefore, it is necessary to improve the work station design by considering human and machine factors. It is then anticipated by making an adjustment between worker, work process and work environment. It is an approach known as ergonomics. Despite its importance to the workers, the company often puts aside the ergonomics aspects for its workers. Working condition not paying attention to the job comfort, satisfaction, safety and health will certainly affect the work productivity. The new design is made by changing the condition of the workplace. The analysis results show the new working condition is better than that of before the redesigning, as seenin the size of work facilities adapted to anthropometry, the procurement of work chairs, desks and ergonomic computers, the decrease of the level of pain complaints at work, the average energy consumptionthat has been smaller after the redesigning. It is expected that workers can feel safe and comfortable and improve their productivity efficiently and effectively.